Damage Detection of a Substructure Based on Response Reconstruction in Frequency Domain - Li, Jun; Law, S.; Ding, Y. (Trans Tech Publications, 2013)
A substructural damage identification approach based on structural response reconstruction in frequency domain is presented. The response reconstruction is based on transforming the measured responses into responses at other locations with the transmissibility matrix and then the relationship between two sets of response vectors is formulated. The damage identification is conducted by minimizing the difference between a measured response vector and the reconstructed response vector. Measured acceleration responses from the damaged substructure and the finite element model of the intact substructure only are required in the identification algorithm. A dynamic response sensitivity-based method with the adaptive Tikhonov regularization technique is adopted for the damage identification with improved results from noisy measurements. A seven-storey frame structure is taken as an example to illustrate the effectiveness and performance of the proposed approach.